1992
DOI: 10.1111/j.1365-2044.1992.tb02389.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper respiratory tract infections and general anaesthesia in children

Abstract: Summary Conjicting reports regarding the hazardr of anaesthesia in children presenting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 12 publications
(5 reference statements)
0
28
1
2
Order By: Relevance
“…62,66,68 Episodes of laryngospasm or bronchospasm in these studies were no more frequent or severe in those with URI. True outcomes such as unanticipated hospital admission, pneumonia, and death were rare.…”
Section: How Serious Are the Respiratory Complications Associated Witmentioning
confidence: 78%
See 2 more Smart Citations
“…62,66,68 Episodes of laryngospasm or bronchospasm in these studies were no more frequent or severe in those with URI. True outcomes such as unanticipated hospital admission, pneumonia, and death were rare.…”
Section: How Serious Are the Respiratory Complications Associated Witmentioning
confidence: 78%
“…60,66 In Tait's prospective cohort of over 1,000 children the definition of "recent" was extended to four weeks. The incidence of adverse respiratory events was 30% in the active URI group, 24.2% in those with symptoms in the past four weeks, and 18% in the control group.…”
Section: How Long After An Uri Should Surgery Be Delayed?mentioning
confidence: 99%
See 1 more Smart Citation
“…HE association between a recent upper respiratory tract infection (URI) and respiratory adverse events, such as bronchospasm, laryngospasm, and hemoglobin desaturation during general anesthesia, has been documented both retrospectively [1][2][3][4] and prospectively. [5][6][7][8] This is a common challenge in pediatric anesthesia, since previous studies have shown a 30-40% prevalence of recent URI in an unselected population presenting for elective surgery. 6,9 Elective surgery may be cancelled because of recent URI, although individual practice varies widely.…”
mentioning
confidence: 99%
“…[5][6][7][8] This is a common challenge in pediatric anesthesia, since previous studies have shown a 30-40% prevalence of recent URI in an unselected population presenting for elective surgery. 6,9 Elective surgery may be cancelled because of recent URI, although individual practice varies widely. 10 The circumvention of complications that cancellation achieves may not justify the inconvenience of postponing a procedure, 11 especially since another URI may develop while awaiting rescheduled surgery -children have an average of six URI per year.…”
mentioning
confidence: 99%